Public health challenges in the context of the influx of refugees from Ukraine to Poland - Sosada, Nicole; Mierzwa, Agnieszka; Syrkiewicz-Świtała, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The new geopolitical situation connected Russia’s invasion of Ukraine has put the Polish healthcare system in front of a huge challenge and the necessity to quickly take and implement strategic decisions aimed at providing the best possible healthcare for refugees without harming the Polish society. Objective: The main objective of the article is to present selected challenges of public health resulting from the influx of refugees to Poland. Materials and methods: the research part used a review of the current Polish literature containing information on the influx of refugees to Poland, Google Scholar, and PubMed scientific databases, as well as statistical data from the Central Statistical Office (CSO). Results: public health, despite many difficulties related to the lack of medical documentation, the threat to the health security of the Polish population, the excessive burden on the state budget, and problems with the implementation of Ukrainian specialists, developed and consistently implemented health strategies with the involvement of private health care. The reforms implemented by the Polish government, aimed at adapting to the new reality, have contributed to the provision of the necessary and specialized health services for refugees, without adversely affecting access to medical care for Polish citizens. Conclusions: The changes introduced by the Polish government, which contributed to the adaptation of the healthcare system to new challenges, such as providing support to refugees, were analyzed. The results of the analysis show that these modifications made it possible to provide the necessary and specialized health services for this group, without affecting the accessibility of healthcare for Polish citizens. The study suggests that such an approach can provide an effective model for adapting to contemporary migration challenges while meeting the needs of refugees and ensuring access to healthcare for the local community.
Keywords: public health; health protection; healthcare; refugee; war; Ukraine